Virulence genes fliC, toxA and phzS are common among Pseudomonas aeruginosa isolates from diabetic foot infections. Issue 4 (3rd April 2018) - Ertugrul, Bulent M.; Oryasin, Erman; Lipsky, Benjamin A.; Willke, Ayşe; Bozdogan, Bulent
Abstract: Background: Outcomes of antibiotic treatment of diabetic foot infections (DFIs) may depend not only on the antimicrobial susceptibility of the aetiologic agents, but also their ability to produce virulence factors. This study aimed to use polymerase chain reaction (PCR) with specific primers to investigate the presence of virulence genes among isolates of Pseudomonas aeruginosa isolates cultured from specimens from diabetic foot and other infections. Methods: We examined 63 P. aeruginosa isolates from inpatients at two University Hospitals for the presence of 23 known bacterial virulence genes, including lasI, lasR, lasA, lasB, rhll, rhlR, rhlAB, aprA, fliC, toxA, plcH, plcN, ExoS, ExoT, ExoU, ExoY, phzI, phzII, phzM, phzS, pvdA, pilA and pilB . Results: Seven virulence genes ( lasl, lasR, lasB, rhll, rhlR, rhlAB and Exo T ) were present in each isolate. No isolate expressed or presented aprA gene. We found that fliC ( p  = .01), toxA ( p  = .041) and phzS ( p  < .001) were statistically and significantly more common in diabetic foot isolates, while plcH ( p  < .001) was significantly more common in other infections. Conclusions: Among clinical isolates of P. aeruginosa from patients with DFIs, three virulence genes that can play important roles in tissue penetration ( fliC), tissue damage and survival under anaerobic condition ( phzS ) and cell death ( toxA ) were significantly more common than isolates from other infections. The Multilocus sequence typing (MLST) analysis of diabetic foot isolates failed to point/indicate the existence of a specific clone or was not able to characterize/identify a specific clone/clonal complex group. Development of new agents to inhibit the synthesis of these genes may improve outcomes in DFIs treatment.